The TGFβ Family in Human Placental Development at the Fetal-Maternal Interface - Chuva de Sousa Lopes, Susana M. (Biomolecules, 2020)
Emerging data suggest that a trophoblast stem cell (TSC) population exists in the early human placenta. However, in vitro stem cell culture models are still in development and it remains under debate how well they reflect primary trophoblast (TB) cells. The absence of robust protocols to generate TSCs from humans has resulted in limited knowledge of the molecular mechanisms that regulate human placental development and TB lineage specification when compared to other human embryonic stem cells (hESCs). As placentation in mouse and human differ considerably, it is only with the development of human-based disease models using TSCs that we will be able to understand the various diseases caused by abnormal placentation in humans, such as preeclampsia. In this review, we summarize the knowledge on normal human placental development, the placental disease preeclampsia, and current stem cell model systems used to mimic TB differentiation. A special focus is given to the transforming growth factor-beta (TGFβ) family as it has been shown that the TGFβ family has an important role in human placental development and disease.